# Check my differentiation please

1. Apr 19, 2005

### krusty the clown

$$y^{(3)}= 2+xy^3$$
$$y^{(4)}=y^3+3xy^2y'$$
$$y^{(5)}=6y^2y'+6xy(y')^2+3xy^2y''$$
$$y^{(6)}=18y(y')^2+6y^2y''+6x(y')^3+12xyy'y''$$

It has been awhile since I have done implicit differentiation, and I am not quite sure if I have used the chain rule properly in each step. I would greatly appreciated any help you could give me on this.

-Erik

2. Apr 19, 2005

### whozum

I'll go through, cant guarantee accuracy though.

$$Third = xy^3 + 2$$

$$Fourth = 3y^2xy' + y^3$$

$$Fifth = 3y^2y' + 3((2xyy'+y^2)y' + y''(y^2x))$$

$$Sixth = 6y(y')^2+y''(3y^2) + 2xyy'y''+y'''(y^2x) + 3((y''(2xyy'+y^2) + y'(y''(2xy)+2yy')+2yy')$$

3. Apr 19, 2005

### whozum

4. Apr 19, 2005

### krusty the clown

thanks, I made a mistake somewhere in the sixth but when I went through it again I still get a different answer than yours. Does that link do implicit differentiation, I didn't see it anywhere. Anyway, it isn't that important. Again, thanks for your help.

Dang, now I am currious...

$$y^{(5)}=6y^2y'+6xy(y')^2+3xy^2y''$$
so for the individual terms we should get
$$(6y^2y')'=12yy'+6y^2y''$$
$$(6xyy'y')'=6yy'y'+6xy'y'y'+6xyy''y'+6xyy'y''$$
$$(3xy^2y'')'=3y^2y''+6xyy''y'+3xy^2y'''$$
added together, I get
$$12yy'+6y^2y''+6y(y')^2+6y(y')^3+18xyy'y''+3y^2y''+3xy^2y'''$$

5. Apr 19, 2005

### whozum

for $$6xy(y')^2$$

I set u = 6xy, v = (y')^2

Then:

$$d(uv)/dx = v du/dx + u dv/dx$$

$$6(y')^2(y+xy') + 6xy(2y'y'')$$

6. Apr 19, 2005

### krusty the clown

If your answer is expanded and mine is compressed they are the same for that term.

Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook